Under the whispering door eaudiobook - Klune, TJ (Macmillan Audio, 2021)
"Narrator Kirt Groves provides an excellently distinct cast of voices." - Locus A Man Called Ove meets The Good Place in Under the Whispering Door , a delightful queer love story from TJ Klune, author of the New York Times and USA Today bestseller The House in the Cerulean Sea . Welcome to Charon's Crossing. The tea is hot, the scones are fresh, and the dead are just passing through. When a reaper comes to collect Wallace from his own funeral, Wallace begins to suspect he might be dead. And when Hugo, the owner of a peculiar tea shop, promises to help him cross over, Wallace decides he's definitely dead. But even in death he's not ready to abandon the life he barely lived, so when Wallace is given one week to cross over, he sets about living a lifetime in seven days. Hilarious, haunting, and kind, Under the Whispering Door is an uplifting story about a life spent at the office and a death spent building a home. "Graves matches his narrative pace to the measured unwinding of the story's layers, focused but unhurried, in the same way that Hugo brews his therapeutic cups of tea." — AudioFile A Macmillan Audio production from Tor Books